ANALISA PENGARUH PERCEIVED EASE OF USE DAN MELALUI PERCEIVED ENJOYMENT TERHADAP BEHAVIOR INTENTION PADA DIGITAL PAYMENT - Feliana Monica; Edwin Japarianto (Jurnal Manajemen Pemasaran, 2022)
The development of information technology in the country of Indonesia continues to experience progress so that the emergence of various breakthroughs in the financial sector. Electronic payment facilities (e-wallet) as one of the developments in the field of financial technology has experienced a rapid increase and is a trend for the people of Indonesia. The various conveniences offered to make everyone very dependent on technology, so e-wallet applications have become a basic necessity for everyone. This study aims to analyze the effect of perceived ease of use on behavioral intention through perceived enjoyment  as an intervening variable on digital payments. The final results obtained in this study indicate that perceived ease of use has a positive effect on behavioral intention, perceived ease of use also has a positive effect on perceived enjoyment, as well as perceived enjoyment has a positive effect on behavior intention. Abstrak: Perkembangan teknologi informasi di negara Indonesia terus mengalami kemajuan sehingga munculnya berbagai terobosan baru di bidang finansial. Sarana pembayaran elektronik (e-wallet) sebagai salah satu perkembangan di bidang financial technology telah mengalami peningkatan pesat dan menjadi kecenderungan bagi masyarakat Indonesia. Berbagai kemudahan yang ditawarkan membuat semua orang sangat bergantung pada teknologi, sehingga aplikasi-aplikasi e-wallet sudah menjadi kebutuhan dasar untuk semua orang. Penelitian ini bertujuan untuk menganalisa pengaruh dari perceived ease of use terhadap behavior intention melalui perceived enjoyment sebagai variabel intervening pada digital payment. Hasil akhir yang diperoleh dalam penelitian ini menunjukkan bahwa perceived ease of use memiliki pengaruh yang positif terhadap behavior intention, perceived ease of use juga memiliki pengaruh yang positif terhadap perceived enjoyment, begitu juga dengan perceived enjoyment memiliki pengaruh yang positif terhadap behavior intention.